Enhancing Nurses' Empathy Towards Young Child Patients Through Empathy Training - Novita Dewi; Frieda Mangunsong (Green Publisher Indonesia, 2024)
In nursing services for early childhood hospitalized patients, nurses' empathetic attitudes cannot be implemented optimally. Empathy is a knowledge and skill that can be improved through education and training programs. Although there are many empathy training programs in nursing, there is no training programs specifically designed to increase nurses' empathy towards early childhood patients. This thesis is a research on an intervention program in the form of the